The anti‐cancer agent SU4312 unexpectedly protects against MPP+‐induced neurotoxicity via selective and direct inhibition of neuronal NOS. (20th February 2013) - Cui, Wei; Zhang, Zaijun; Li, Wenming; Hu, Shengquan; Mak, Shinghung; Zhang, Huan; Han, Renwen; Yuan, Shuai; Li, Sai; Sa, Fei; Xu, Daping; Lin, Zhixiu; et al.
Abstract : Background and Purpose: SU4312, a potent and selective inhibitor of VEGF receptor‐2 (VEGFR‐2), has been designed to treat cancer. Recent studies have suggested that SU4312 can also be useful in treating neurodegenerative disorders. In this study, we assessed neuroprotection by SU4312 against 1‐methyl‐4‐phenylpyridinium ion (MPP + )‐induced neurotoxicity and further explored the underlying mechanisms. Experimental Approach: MPP + ‐treated neurons and 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP)‐treated zebrafish were used to study neuroprotection by SU4312. NOS activity was assayed in vitro to examine direct interactions between SU4312 and NOS isoforms. Key Results: SU4312 unexpectedly prevented MPP + ‐induced neuronal apoptosis in vitro and decreased MPTP‐induced loss of dopaminergic neurons, reduced expression of mRNA for tyrosine hydroxylase and impaired swimming behaviour in zebrafish. In contrast, PTK787/ZK222584, a well‐studied VEGFR‐2 inhibitor, failed to prevent neurotoxicity, suggesting that the neuroprotective actions of SU4312 were independent of its anti‐angiogenic action. Furthermore, SU4312 exhibited non‐competitive inhibition of purified neuronal NOS (nNOS) with an IC50 value of 19.0 μM but showed little or no effects on inducible and endothelial NOS. Molecular docking simulations suggested an interaction between SU4312 and the haem group within the active centre of nNOS. Conclusions and Implication: SU4312 exhibited neuroprotection against MPP + at least partly via selective and direct inhibition of nNOS. Because SU4312 could reach the brain in rats, our study also offered a support for further development of SU4312 to treat neurodegenerative disorders, particularly those associated with NO‐mediated neurotoxicity.